Evaluation of The Implementation of Group Guidance Services at SMA Negeri 2 Merangin - Ramadhan, Andra; Kardo, Rici; Imelda Usman, Citra (Lembaga Riset Mutiara Akbar, 2022)
The background of this research is that there has not been an evaluation of group guidance services carried out by BK teachers at SMA Negeri 2 Merangin so that the success of the group guidance services provided has not been measured in terms of effectiveness and success. This study aims to describe: 1) Evaluation of the implementation of group guidance services at SMA Negeri 2 Merangin seen from the evaluation process, 2) Evaluation of the implementation of group guidance services at SMA Negeri 2 Merangin seen from the evaluation of results. This type of research is descriptive quantitative. The population of this study were all students of class XI IPS SMA Negeri 2 Merangin who were members of the group guidance service group. The sampling technique was carried out with a total sampling of 29 people. The research data was obtained through a questionnaire which was analyzed using the percentage technique. The results of this study on the evaluation of the implementation of group guidance services at SMA Negeri 2 Merangin which showed that: 1) the evaluation of the implementation of group guidance services at SMA Negeri 2 Merangin was in the good category with a percentage of 44.83%. 2) evaluation of the implementation of group guidance services at SMA Negeri 2 Merangin seen from the evaluation results are in the good category with a percentage of 44.83%. This research is recommended for BK teachers to evaluate guidance and counseling services, especially group guidance services on a regular basis, because through this evaluation teachers can get information about the success of the services provided